Facile synthesis of Ag/Zn1-xCuxO nanoparticle compound photocatalyst for high-efficiency photocatalytic degradation: Insights into the synergies and antagonisms between Cu and Ag. Issue 1 (1st January 2021) - Luo, Kaiyi; Zhang, Qiuping; Yuan, Huan; Liu, Yutong; Wang, Xiaoyi; Zhang, Jiaxi; Hu, Wenyu; Xu, Ming; Xu, Shuyan; Levchenko, Igor; Bazaka, Kateryna
Abstract: By carefully balancing synergies and antagonisms that arise from incorporating Cu and Ag within a single ZnO-based catalytic platform, the photocatalytic activity of Ag/ZnO based on three-dimensional modified ceramic structures can be further significantly enhanced. The performance of Ag/ZnO heterostructure (Z0) was significantly improved by only 0.2 mol% Cu incorporation (Z0.2) and the first-order degradation kinetics constants (K) of Z0.2 were 2 and 1.5 times higher than that of Z0 under simulated sunlight and UV light. The synergies between Cu dopants and metallic Ag were mainly the significantly enhanced visible light absorption capacity and the prolonged photo-excited charge lifetime. However, with the excessive introduction of Cu precursors, the surface Cu 2+ was found to inhibit the interfacial charge transfer between Ag and ZnO NPs under UV and visible light irradiation, but the transformation from Cu 2+ to Cu + was also presumed to be a driving factor for the improvement of photocatalytic efficiency. These interactions may provide a useful pathway for enhancing photocatalytic efficiency of low-cost ZnO-based catalytic platforms.